Light photography concept for the album design of Pipe Dreams by Jim Walker and The MacEwan Generations Big Band - Hussein, Daenya (My University, 2023)
The album Pipe Dreams by Jim Walker and The MacEwan Generations Big Band captures the fluidity and essence of Jazz and Big Band in one record. We hear notes of South American, East Indian, and Celtic vibes to start the unique record off. The fusion of Jazz and Big Band in the album has a mix of energy, excitement, and spontaneity in Jazz but the controlled discipline of Big Band. The concept for the album's design was to capture the two sensations of sound and movement into one cohesive creation. Light photography was used to display the feeling of movement and energy captured from the album. As a soft reminder of the tones used in the first three tracks, the use of dominant flag colours of Brazil, India, Wales, Ireland, and Scotland are displayed in the light painting. To keep a consistent tone, the typeface Abril Fatface is used to echo the feel of Big Band and Century Gothic for the secondary header to keep the balance. As the light painting streaks across the cover, it guides the viewer to the back with the title tracks and the continuation of the light painting. As we open the album, we slide out the record and insert to see the consistent use of light painting at a macro scale. The use of complementary colours, orange and blue, as subtle reminders of the colours in the light painting from the album cover.
Presented on April 20, 2023 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: album design; package design